Experimental evaluation of effects of steel and glass fibers on engineering properties of concrete - Jalal Akbari; Amirhossein Abed (Fracture and Structural Integrity)
This paper experimentally investigates the effect of steel and glass fibers on the engineering properties of concrete. To achieve this, 0.3%, 0.6%, and 0.9% by volume fraction of steel and glass fibers are added in concrete mixtures with water-to-cement (W/C) ratios 0.35 and 0.45. For each ratio of water to cement, 21 cubic samples for compressive strength tests, 14 cylindrical samples for tension strength tests, and also 14 prismatic samples for three-point flexural strength tests were prepared. The experimental results show that adding 0.3% to 0.9% % steel fibers for concrete increases simultaneously the compressive, tension, and also flexural strengths in comparison with plain concrete. Adding glass fibers only between 0.3% to 0.6% increases the compressive strength. The results reveal that the best range for reinforcing concrete with steel fiber is 0.3% to 0.9 %, and glass fiber is 0.3% to 0.6 % by volume fraction of fiber to improve the engineering strengths concrete. As a rule of thumb, the tension and flexural strengths of concrete could be explained as 8% and 13% of the compressive strength, respectively.